Non-aqueous electrolyte secondary battery
By incorporating a specific volume percentage of gel-forming polymer and controlling discharge depth, the battery maintains capacity and stability over multiple cycles, addressing the capacity loss issue in non-aqueous electrolyte secondary batteries.
Patent Information
- Application Number
- JP2023092360
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing non-aqueous electrolyte secondary batteries suffer from a decrease in capacity after cycling, despite improvements in cycle durability techniques.
The battery design includes an electrode active material layer with a controlled volume percentage of gel-forming polymer (6.9≦y≦7.8%) and a maximum discharge depth (DOD max 89≦DOD max ≦99%) to stabilize the electrode structure during charging and discharging.
This configuration effectively suppresses the decrease in capacity over cycling, ensuring long-term durability and performance.
Smart Images

Figure 2024174503000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, the spread of various electric vehicles is expected to help solve environmental and energy problems. Secondary batteries have been developed as on-board power sources, such as motor drive power sources, which are key to the spread of these electric vehicles. Non-aqueous electrolyte secondary batteries intended for use as on-board power sources are required to have high capacity, excellent cycle durability, and output characteristics (rate characteristics).
[0003] Conventionally, as a technique for improving the cycle durability of secondary batteries, Patent Document 1 discloses a technique for controlling the mass ratio of the non-aqueous electrolyte to the mass of silicon contained in the negative electrode active material layer in a non-aqueous electrolyte secondary battery using a mixed negative electrode active material of silicon oxide and graphite to a predetermined value or more. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-63671 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, according to the studies of the present inventors, it has become clear that in the secondary battery described in Patent Document 1, a decrease in capacity after cycle durability is still unavoidable, and there is still room for improvement.
[0006] Therefore, an object of the present invention is to provide a means for further suppressing the decrease in capacity of a non-aqueous electrolyte secondary battery after endurance cycling. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems, and have found that it is effective to control the volume percentage of the gel-forming polymer contained in the electrode active material layer to a value within a predetermined range and to control the maximum value of the depth of discharge (DOD) during discharge of the battery to a value within a predetermined range in a nonaqueous electrolyte secondary battery using an electrolyte and an electrode having an electrode active material layer containing a gel-forming polymer, thereby completing the present invention.
[0008] That is, the nonaqueous electrolyte secondary battery according to the present invention has an electrode in which an electrode active material layer containing an electrode active material and a gel-forming polymer is disposed on the surface of a current collector, and an electrolyte layer in which a separator disposed adjacent to the electrode active material layer is impregnated with an electrolyte solution. Here, the nonaqueous electrolyte secondary battery has a volume percentage y [%] of the gel-forming polymer contained in the electrode active material layer that satisfies 6.9≦y≦7.8, and a maximum depth of discharge (DOD) during discharge DOD max [%] is 89 or less DOD max It is characterized by being used to satisfy the condition ≦99. Effect of the Invention
[0009] According to the present invention, it is possible to further suppress the decrease in capacity of a nonaqueous electrolyte secondary battery after cycle durability. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view showing a schematic diagram of a stacked (flat) non-bipolar (internal parallel connection) secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] One embodiment of the present invention is an electrode comprising an electrode active material layer including an electrode active material and a gel-forming polymer disposed on the surface of a current collector, and an electrolyte layer formed by impregnating an electrolyte solution in a separator disposed adjacent to the electrode active material layer, the volume percentage y [%] of the gel-forming polymer contained in the electrode active material layer satisfying 6.9≦y≦7.8, and the maximum depth of discharge (DOD) during discharge is 0.01 to 0.15. max [%] is 89 or less DOD max ≦99.
[0012] Another embodiment of the present invention is a method for using a non-aqueous electrolyte secondary battery having an electrode in which an electrode active material layer containing an electrode active material and a gel-forming polymer is disposed on the surface of a current collector, and an electrolyte layer in which a separator disposed adjacent to the electrode active material layer is impregnated with an electrolyte solution, the volume percentage y [%] of the gel-forming polymer contained in the electrode active material layer satisfying 6.9≦y≦7.8, max [%] is 89 or less DOD max This is a method of use in which discharge is performed so that the discharge rate satisfies the condition of ≦99.
[0013] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the claims and is not limited to the following embodiments. The dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios. In this specification, the range "X to Y" means "X or more and Y or less." Furthermore, unless otherwise specified, the operation and measurement of physical properties are performed under the conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.
[0014] FIG. 1 is a cross-sectional view that illustrates a flat (laminated) non-bipolar (internal parallel connection) secondary battery (hereinafter also simply referred to as a "laminated secondary battery") according to one embodiment of the present invention.
[0015] As shown in Fig. 1, the stacked secondary battery 10a of this embodiment has a structure in which a substantially rectangular power generating element 21, in which a charge / discharge reaction actually proceeds, is sealed inside a laminate film 29. Here, the power generating element 21 has a configuration in which a positive electrode in which a positive electrode active material layer 13 is arranged on both sides of a positive electrode collector 11', an electrolyte layer 17 made of a separator containing an electrolytic solution, and a negative electrode in which a negative electrode active material layer 15 is arranged on both sides of a negative electrode collector 12 are laminated. Specifically, the positive electrode, the electrolyte layer, and the negative electrode are laminated in this order, with one positive electrode active material layer 13 and the adjacent negative electrode active material layer 15 facing each other with the electrolyte layer 17 interposed therebetween.
[0016] As a result, the positive electrode, the electrolyte layer, and the negative electrode form one unit cell layer 19. Therefore, the stacked secondary battery 10a shown in FIG. 1 can be said to have a configuration in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel. The positive electrode current collectors of the outermost layers located on both outermost layers of the power generating element 21 each have the positive electrode active material layer 13 disposed on only one side, but active material layers may be provided on both sides. That is, instead of using a current collector dedicated to the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as the current collector of the outermost layer as it is. Also, by reversing the arrangement of the positive electrode and the negative electrode from FIG. 1, the outermost negative electrode current collector may be located on both outermost layers of the power generating element 21, and the negative electrode active material layer may be disposed on one or both sides of the outermost negative electrode current collector.
[0017] A positive electrode current collector 25 and a negative electrode current collector 27 that are electrically connected to the electrodes (positive and negative electrodes) are attached to the positive electrode current collector 11' and the negative electrode current collector 12, respectively, and are structured to be sandwiched between the ends of the laminate film 29 and led out of the laminate film 29. The positive electrode current collector 25 and the negative electrode current collector 27 may be attached to the positive electrode current collector 11' and the negative electrode current collector 12 of the electrodes by ultrasonic welding, resistance welding, or the like, respectively, via a positive electrode terminal lead and a negative electrode terminal lead (not shown) as necessary.
[0018] The main components of the nonaqueous electrolyte secondary battery according to this embodiment will be described below.
[0019] [electrode] The electrode has a configuration in which an electrode active material layer containing an electrode active material and a gel-forming polymer is disposed on the surface of a current collector.
[0020] [Current collector] The current collector has a function of mediating the movement of electrons from one surface in contact with the positive electrode active material layer to the other surface in contact with the negative electrode active material layer. There are no particular limitations on the material constituting the current collector, but for example, metals and conductive resins can be used.
[0021] Specifically, metals include aluminum, nickel, iron, stainless steel, titanium, and copper. In addition to these, a clad material of nickel and aluminum, a clad material of copper and aluminum, or a plated material of a combination of these metals can be preferably used. Also, a foil in which a metal surface is coated with aluminum, or a carbon-coated aluminum foil may be used. Among them, aluminum, stainless steel, copper, and nickel are preferred from the viewpoint of electronic conductivity and battery operating potential.
[0022] The latter conductive resin may be a conductive polymer material or a non-conductive polymer material to which a conductive filler is added as necessary. Examples of conductive polymer materials include polyaniline, polypyrrole, polythiophene, polyacetylene, polyparaphenylene, polyphenylenevinylene, polyacrylonitrile, and polyoxadiazole. Such conductive polymer materials have sufficient conductivity even without the addition of conductive fillers, and are therefore advantageous in terms of facilitating the manufacturing process or reducing the weight of the current collector.
[0023] Examples of non-conductive polymeric materials include polyethylene (PE; high density polyethylene (HDPE), low density polyethylene (LDPE), etc.), polypropylene (PP), polyethylene terephthalate (PET), polyethernitrile (PEN), polyimide (PI), polyamideimide (PAI), polyamide (PA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), polyvinylidene fluoride (PVdF), polystyrene (PS), etc. Such non-conductive polymeric materials can have excellent electric potential resistance or solvent resistance.
[0024] A conductive filler may be added to the conductive polymer material or non-conductive polymer material as necessary. In particular, when the resin serving as the base material of the current collector is made of only a non-conductive polymer, a conductive filler is necessarily required to impart conductivity to the resin.
[0025] The conductive filler can be used without any particular limitation as long as it is a material having electrical conductivity. For example, metals and conductive carbons can be mentioned as materials having excellent electrical conductivity, potential resistance, or lithium ion blocking properties. The metal is not particularly limited, but preferably contains at least one metal selected from the group consisting of Ni, Ti, Al, Cu, Pt, Fe, Cr, Sn, Zn, In, Sb, and K, or an alloy or metal oxide containing these metals. The conductive carbon is also not particularly limited. Preferably, it contains at least one selected from the group consisting of acetylene black, Vulcan (registered trademark), Black Pearl (registered trademark), carbon nanofiber, Ketjen Black (registered trademark), carbon nanotube, carbon nanohorn, carbon nanoballoon, and fullerene.
[0026] The amount of conductive filler added is not particularly limited as long as it is an amount that can impart sufficient conductivity to the current collector, and is generally about 5 to 80 mass %.
[0027] The current collector may be a single layer structure made of a single material, or may be a laminate structure made of a suitable combination of layers made of these materials. From the viewpoint of reducing the weight of the current collector, it is preferable that the current collector includes at least a conductive resin layer made of a resin having electrical conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector.
[0028] [Electrode active material layer] The electrode active material layer is disposed on the surface of the current collector, and contains an electrode active material (a positive electrode active material or a negative electrode active material) and a gel-forming polymer.
[0029] (Cathode active material) The positive electrode active material has a function of releasing ions such as lithium ions during charging and absorbing ions such as lithium ions during discharging. In the nonaqueous electrolyte secondary battery according to the present embodiment, the type of the positive electrode active material is not particularly limited. From the viewpoint of having a higher capacity, it is preferable that the positive electrode active material is made of the space group R3m. The positive electrode active material belonging to the space group R3m has a layered structure (layered rock salt structure) in which lithium atomic layers and transition metal atomic layers are alternately stacked. Therefore, by using such a positive electrode active material, the battery capacity of the nonaqueous electrolyte secondary battery can be improved.
[0030] Examples of the positive electrode active material belonging to the space group R3m include lithium-transition metal composite oxides such as LiCoO2, LiNiO2, LiMnO2, Li(Ni-Mn-Co)O2, Li(Ni-Co-Al)O2, and those in which a part of these transition metals is replaced by other elements. In some cases, two or more positive electrode active materials may be used in combination. More preferably, a composite oxide containing lithium and nickel is used, and even more preferably, Li(Ni-Mn-Co)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter, also simply referred to as "NMC composite oxide") or Li(Ni-Co-Al)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter, also simply referred to as "NCA composite oxide") is used, and particularly preferably, NMC composite oxide is used.
[0031] As described above, the NMC composite oxide and the NCA composite oxide also include composite oxides in which a part of the transition metal element is replaced by another metal element. In this case, the other elements include Al, Sn, Nb, Ti, Zr, Mg, W, P, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, V, Cu, Ag, Zn, etc., and are preferably Al, Sn, Nb, Ti, Zr, Mg, W, P, V, Ca, Sr, Cr, more preferably Al, Sn, Nb, Ti, Zr, Mg, P, Cr, and further preferably Al, Sn, Nb, Ti, Zr, Mg, from the viewpoint of improving cycle characteristics. However, the other metal elements that can replace the transition metal element of the NCA composite oxide are other than Al.
[0032] The lithium-transition metal composite oxide as the positive electrode active material particles has a high theoretical discharge capacity, and therefore is preferably represented by the general formula (1): Li x Ni a M b N c O2 (wherein x, a, b, c, and d satisfy 0.8≦x≦1.1, a+b+c=1, 0.33≦a≦0.95, 00.05≦b≦0.67, and 0≦c≦0.10. M is one or more elements selected from the group consisting of Mn and Co, and N is one or more elements selected from the group consisting of Al, Sn, Nb, Ti, Zr, and Mg). Here, x represents the atomic ratio of Li, a represents the atomic ratio of Ni, b represents the atomic ratio of M, and c represents the atomic ratio of N. The composition of each element can be measured, for example, by plasma (ICP) emission spectrometry. From the viewpoint of realizing a higher discharge capacity, it is preferable that in the general formula (1), 0.80≦a≦0.95 (i.e., high nickel composite oxide).
[0033] From the viewpoint of achieving high output, the average particle diameter (D50) of the positive electrode active material is preferably 1 to 100 μm, and more preferably 1 to 20 μm. In this specification, the average particle diameter (D50) is measured by a particle size distribution measuring device using a laser diffraction / scattering method.
[0034] (Negative electrode active material) Examples of the negative electrode active material include carbon materials such as graphite, soft carbon, and hard carbon, and lithium-transition metal composite oxides (e.g., Li4Ti5O 12 ), metal materials such as silicon-based negative electrode active materials and tin-based negative electrode active materials, and lithium alloy-based negative electrode materials (for example, lithium-tin alloys, lithium-silicon alloys, lithium-aluminum alloys, lithium-aluminum-manganese alloys, etc.). In some cases, two or more types of negative electrode active materials may be used in combination. From the viewpoints of capacity and output characteristics, carbon materials, metal materials, lithium-transition metal composite oxides, and lithium alloy-based negative electrode materials are preferably used as the negative electrode active materials.
[0035] In a preferred embodiment, the negative electrode active material includes a silicon-based negative electrode active material or a tin-based negative electrode active material, more preferably a silicon-based negative electrode active material. In this way, it is a preferred embodiment of the nonaqueous electrolyte secondary battery according to the present embodiment that the electrode active material layer is a negative electrode active material layer containing a silicon-based negative electrode active material as the electrode active material.
[0036] Here, silicon and tin belong to the 14th group of elements, and are known to be negative electrode active materials that can greatly improve the capacity of non-aqueous electrolyte secondary batteries. These simple substances can absorb and release a large number of charge carriers (lithium ions, etc.) per unit volume (mass), and therefore can be high-capacity negative electrode active materials. Here, simple Si can be used as the silicon-based negative electrode active material. In addition, from the viewpoint of increasing capacity, SiO 2 disproportionated into two phases, a Si phase and a silicon oxide phase, can be used. xIt is also preferable to use silicon oxide such as (0.3≦x≦1.6). In this case, the range of x is more preferably 0.5≦x≦1.5, and further preferably 0.7≦x≦1.2. Furthermore, an alloy containing silicon (silicon-containing alloy-based negative electrode active material) may be used. On the other hand, examples of the negative electrode active material containing tin element (tin-based negative electrode active material) include simple Sn, tin alloys (Cu-Sn alloys, Co-Sn alloys), amorphous tin oxide, and tin silicon oxide. In addition, when the negative electrode active material contains a silicon-based negative electrode active material or a tin-based negative electrode active material (more preferably contains a silicon-based negative electrode active material), the content ratio of the silicon-based negative electrode active material or the tin-based negative electrode active material (preferably a silicon-based negative electrode active material, more preferably a silicon oxide) in the negative electrode active material is preferably more than 0 mass% and 5 mass% or less. Generally, silicon-based negative electrode active materials and tin-based negative electrode active materials undergo large volume changes due to expansion and contraction during the charge and discharge process, but by including these negative electrode active materials in such amounts, the gel-forming polymer can fully follow the volume changes of these active materials. As a result, it becomes possible to fully enjoy the benefits of using these active materials, such as high capacity and high output. In addition, when the negative electrode active material includes these active materials, it is preferable that the main component of the negative electrode active material is a carbon material such as graphite.
[0037] The average particle size (D50) of the negative electrode active material is not particularly limited, but from the viewpoint of achieving high output, it is preferably 1 to 100 μm, more preferably 1 to 20 μm.
[0038] In the electrode active material layer, the content of the electrode active material (converted into solid content) is preferably 60 to 95 mass %, more preferably 80 to 95 mass %, from the viewpoint of output characteristics.
[0039] (Gel-forming polymer) The gel-forming polymer is an ion-conductive polymer, and can form a structure together with the electrode active material to play a role in ion conduction. The gel-forming polymer also functions as a binder in the electrode active material layer. Therefore, when the electrode active material layer contains a gel-forming polymer, the retention of the electrolyte in the electrode active material layer is increased, which contributes to improving the rate characteristics of the battery. From the viewpoint of output characteristics, the gel-forming polymer may be at least one selected from the group consisting of polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene (PVdF-HEP), polymethyl methacrylate (PMMA), polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, polypropylene glycol dimethacrylate, polypropylene glycol diacrylate, polymethyl methacrylate, and copolymers thereof.
[0040] From the viewpoint of further improving the output characteristics, the gel-forming polymer preferably contains at least one selected from polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene (PVdF-HEP) and polymethyl methacrylate (PMMA), and more preferably contains polyvinylidene fluoride-hexafluoropropylene (PVdF-HEP). When the gel-forming polymer contains PVdF-HEP, the cycle durability of the nonaqueous electrolyte secondary battery can be further improved.
[0041] There is no particular restriction on the physical properties of the gel-forming polymer, but the tensile break strength (ASTM D638 / 23°C) of the gel-forming polymer is preferably 25 to 54 [MPa]. If the tensile break strength of the gel-forming polymer is 25 [MPa] or more, sufficient adhesive strength can be exhibited between the gel-forming polymer and the active material, and the collapse of the electrode active material layer during the expansion and contraction of the active material can be effectively prevented. On the other hand, if the tensile break strength of the gel-forming polymer is 54 [MPa] or less, the break of the polymer during the expansion of the active material is prevented, and the electrolyte can be held in a state of being sufficiently adhered to the periphery of the active material. In addition, the yield tensile elongation, yield tensile strength, tensile elongation at break (all ASTM D638 / 23°C) and compressive strength (ASTM D695 / 23°C) of the gel-forming polymer are preferably 5 to 15 [%], 31 to 41 [MPa], 30 to 200 [%] and 41 to 58 [MPa], respectively.
[0042] In the non-aqueous electrolyte secondary battery according to the present embodiment, the volume percentage y [%] of the gel-forming polymer contained in the electrode active material layer must satisfy 6.9≦y≦7.8, preferably 7.2≦y≦7.8, and more preferably 7.2≦y≦7.4. If y is less than 6.9 [%], the binding between the components contained in the electrode active material layer is reduced, and there is a risk of a decrease in capacity characteristics due to the expansion and contraction of the active material accompanying the progress of charging and discharging. On the other hand, if y exceeds 7.8 [%], the presence of the gel-forming polymer itself leads to an increase in the electrical resistance of the electrode active material layer, and the decrease in the capacity of the battery after cycle endurance cannot be sufficiently suppressed. The value of y can be controlled by the amount of gel-forming polymer charged when the battery is produced. In addition, the volume percentage (y [%]) of the gel-forming polymer contained in the electrode active material layer is calculated by the method described in the Examples section below.
[0043] The liquid absorption rate (z) of the gel-forming polymer with respect to the electrolytic solution is preferably more than 15%, more preferably 30% or more, and still more preferably 40% or more. The upper limit of the liquid absorption rate of the gel-forming polymer with respect to the electrolytic solution is not particularly limited, but is preferably less than 90%, more preferably 70% or less, and still more preferably 50% or less. When the liquid absorption rate of the gel-forming polymer with respect to the electrolytic solution is more than 15%, the gel-forming polymer can sufficiently hold the electrolytic solution, so that it can be responsible for ion conduction. When the liquid absorption rate of the gel-forming polymer with respect to the electrolytic solution is less than 90%, the structure with the electrode active material can be sufficiently maintained. That is, in one embodiment of the present invention, it is preferable that the breaking strength of the gel-forming polymer is 25 to 54 [MPa], and the liquid absorption rate (z) of the gel-forming polymer with respect to the electrolytic solution satisfies 15 < z < 90. By adopting such a configuration, the action and effect of the present invention can be more effectively exhibited. The liquid absorption rate of the gel-forming polymer with respect to the electrolytic solution shall be calculated by the method described in the Examples section below.
[0044] The percentage x [%] of the volume of pores in the electrode active material layer is not particularly limited, and is, for example, 15 to 45 [%], preferably 20 to 40 [%], and still more preferably 25 to 35 [%]. x can be adjusted by the particle size of the electrode active material, the charged amount of the gel-forming polymer, the film thickness of the electrode active material layer, etc. Also, as described later, it can be adjusted by the presence or absence of the pressing treatment during electrode production and the conditions of the pressing treatment. The percentage (x [%]) of the volume of pores in the electrode active material layer shall be calculated by the method described in the Examples section below.
[0045] Also, in a preferred embodiment of the non-aqueous electrolyte secondary battery according to this embodiment, a preferred range of (x + y) is defined. That is, x and y described above preferably satisfy 30.8 ≦ x + y ≦ 38.9, and more preferably satisfy 34.4 ≦ x + y ≦ 36.2. A non-aqueous electrolyte secondary battery satisfying these configurations is preferable because the action and effect of the present invention, such as a decrease in capacity after cycle durability, can be more remarkably exhibited.
[0046] (Conductive assistant) The electrode active material layer may further contain a conductive assistant.
[0047] The conductive assistant has a function of forming an electron conduction path (conductive passage) in the electrode active material layer. When such an electron conduction path is formed in the electrode active material layer, the internal resistance of the battery is reduced, which can contribute to improving the output characteristics at a high rate. In particular, it is preferable that at least a part of the conductive assistant forms a conductive passage that electrically connects the two main surfaces of the electrode active material layer (in this embodiment, a conductive passage that electrically connects from the first main surface in contact with the electrolyte layer side of the electrode active material layer to the second main surface in contact with the current collector side is formed). By having such a form, the electron transfer resistance in the thickness direction in the electrode active material layer is further reduced, so that the output characteristics at a high rate of the battery can be further improved. Note that whether or not at least a part of the conductive assistant forms a conductive passage that electrically connects the two main surfaces of the electrode active material layer (in this embodiment, a conductive passage that electrically connects from the first main surface in contact with the electrolyte layer side of the electrode active material layer to the second main surface in contact with the current collector side is formed) can be confirmed by observing the cross section of the electrode active material layer using an SEM or an optical microscope.
[0048] From the viewpoint of reliably forming such a conductive path, the conductive assistant is preferably a conductive fiber having a fibrous form.Specific examples include carbon fibers such as PAN-based carbon fibers and pitch-based carbon fibers, conductive fibers made by uniformly dispersing metals or graphite with good conductivity in synthetic fibers, metal fibers made by fiberizing metals such as stainless steel, conductive fibers made by coating the surface of organic fibers with metal, and conductive fibers made by coating the surface of organic fibers with resin containing a conductive material.Among them, carbon fibers are preferred because they are excellent in conductivity and lightweight.
[0049] However, a conductive assistant that does not have a fibrous form may be used. For example, a conductive assistant having a particulate (e.g., spherical) form may be used. When the conductive assistant is particulate, the shape of the particles is not particularly limited, and may be any shape such as powder, sphere, plate, column, irregular shape, scale, spindle, etc. When the conductive assistant is particulate, the average particle diameter (primary particle diameter) is not particularly limited, but is preferably about 0.01 to 10 μm from the viewpoint of the electrical characteristics of the battery. The "particle diameter of the conductive assistant" means the maximum distance L among the distances between any two points on the contour line of the conductive assistant. The value of the "average particle diameter" is calculated as the average value of the particle diameters of particles observed in several to several tens of fields of view using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0050] Examples of conductive assistants having a particulate (e.g., spherical) form include, but are not limited to, metals such as aluminum, stainless steel (SUS), silver, gold, copper, and titanium, alloys or metal oxides containing these metals, and carbon such as carbon nanotubes (CNTs) and carbon black (specifically, acetylene black, Ketjen Black (registered trademark), furnace black, channel black, thermal lamp black, etc.). In addition, a conductive assistant can be used in which the above-mentioned metal material is coated around a particulate ceramic material or resin material by plating or the like. Among these conductive assistants, from the viewpoint of electrical stability, it is preferable to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, copper, titanium, and carbon, more preferably to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, and carbon, and even more preferably to include at least one carbon. These conductive assistants may be used alone or in combination of two or more.
[0051] The content of the conductive assistant in the electrode active material layer is preferably 0.1 to 5 mass %, and more preferably 0.2 to 2 mass %, relative to 100 mass % of the total solid content of the electrode active material layer (total solid content of all components). When the content of the conductive assistant is within the above range, there is an advantage that an electron conduction path can be well formed in the electrode active material layer and a decrease in the energy density of the battery can be suppressed.
[0052] In a preferred embodiment of the present invention, the electrode active material layer includes a structure made of an electrode active material, a gel-forming polymer, and a conductive assistant. This allows the electrode active material to be in good contact with the conductive assistant, and the electrode active material to be in an active state, thereby further improving electronic conduction. In addition, by structuring the conductive assistant around the electrode active material, excellent conductivity can be ensured, and output characteristics and capacity characteristics can be improved. Furthermore, by structuring the conductive assistant around the electrode active material, percolation in the pores is formed. Therefore, the effective ion conductivity can be further improved. In addition, by making such a structure, the electrode active material layer can be made into a free-standing film, and the strength of the electrode can be further increased.
[0053] The thickness of the electrode active material layer is usually about 1 to 1000 μm, preferably 20 to 800 μm, more preferably 30 to 500 μm, and further preferably 40 to 200 μm. If the thickness of the electrode active material layer is equal to or greater than the above-mentioned lower limit, the energy density of the battery can be sufficiently increased. On the other hand, if the thickness of the electrode active material layer is equal to or less than the above-mentioned upper limit, the structure of the electrode active material layer can be sufficiently maintained.
[0054] In this embodiment, the electrode active material layer can improve mechanical strength by structuring the electrode active material and the gel-forming polymer (and the conductive assistant). Therefore, even if the thickness of the electrode is increased, the mechanical strength of the electrode can be improved while maintaining excellent output characteristics.
[0055] [Electrolyte layer] The electrolyte layer has a configuration in which a separator arranged adjacent to an electrode active material layer constituting an electrode is impregnated with an electrolytic solution. Note that the term "adjacent to" the electrode active material layer does not necessarily mean that the separator is arranged directly adjacent to the electrode active material layer, but also includes the concept of being arranged with another layer interposed between the separator and the electrode active material layer as necessary.
[0056] The electrolyte functions as a carrier for lithium ions. The electrolyte constituting the electrolyte layer has a form in which a lithium salt is dissolved in a non-aqueous solvent.
[0057] Examples of non-aqueous solvents include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propionate (MP), methyl acetate (MA), methyl formate (MF), 4-methyldioxolane (4MeDOL), dioxolane (DOL), 2-methyltetrahydrofuran (2MeTHF), tetrahydrofuran (THF), dimethoxyethane (DME), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and γ-butyrolactone (GBL). Among them, the non-aqueous solvent is preferably dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), and preferably contains ethylene carbonate. The non-aqueous solvent to be added may be used alone or in combination of two or more kinds.
[0058] Examples of lithium salts include LiN(FSO2)2, Li(C2F5SO2)2N, LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, etc. Among these, from the viewpoint of battery output and charge / discharge cycle characteristics, LiN(FSO2)2 is more preferable.
[0059] The concentration of the lithium salt in the electrolyte is preferably 0.1 to 3.0 mol / L, and more preferably 0.8 to 2.2 mol / L.
[0060] The electrolyte may further contain additives other than the above-mentioned components. The additives may be contained in the electrolyte. Specific examples of such compounds include vinylene carbonate, methylvinylene carbonate, dimethylvinylene carbonate, phenylvinylene carbonate, diphenylvinylene carbonate, ethylvinylene carbonate, diethylvinylene carbonate, vinylethylene carbonate, 1,2-divinylethylene carbonate, 1-methyl-1-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-1-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, and the like. ester, vinyl vinylene carbonate, allyl ethylene carbonate, vinyloxymethyl ethylene carbonate, allyloxymethyl ethylene carbonate, acryloxymethyl ethylene carbonate, methacryloxymethyl ethylene carbonate, ethynyl ethylene carbonate, propargyl ethylene carbonate, ethynyloxymethyl ethylene carbonate, propargyloxyethylene carbonate, methylene ethylene carbonate, 1,1-dimethyl-2-methylene ethylene carbonate, etc. These additives may be used alone or in combination of two or more. In addition, the amount of additive used in the electrolyte is preferably 0.5 to 10 mass%, more preferably 0.5 to 5 mass%, based on 100 mass% of the electrolyte before the additive is added.
[0061] In the nonaqueous electrolyte secondary battery according to the present embodiment, a separator is used in the electrolyte layer. The separator has a function of retaining the electrolyte to ensure lithium ion conductivity between the positive electrode and the negative electrode, and a function of acting as a partition between the positive electrode and the negative electrode.
[0062] The separator may be in the form of, for example, a porous sheet separator made of a polymer or fiber capable of absorbing and retaining the electrolyte, or a nonwoven fabric separator.
[0063] As the separator of the porous sheet made of polymer or fiber, for example, a microporous (microporous membrane) can be used. Specific forms of the porous sheet made of the polymer or fiber include, for example, polyolefins such as polyethylene (PE) and polypropylene (PP); laminates of a plurality of these laminates (for example, a laminate having a three-layer structure of PP / PE / PP), polyimide, aramid, hydrocarbon resins such as polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP), glass fibers, etc., and microporous (microporous membrane) separators can be mentioned.
[0064] The thickness of the microporous (microporous membrane) separator cannot be unequivocally defined because it varies depending on the application. For example, in applications such as motor-driven secondary batteries for electric vehicles (EVs), hybrid electric vehicles (HEVs), and fuel cell vehicles (FCVs), the thickness is preferably 4 to 60 μm for single or multi-layered structures. The micropore diameter of the microporous (microporous membrane) separator is preferably 1 μm or less at maximum (usually a pore diameter of about several tens of nm).
[0065] As the nonwoven fabric separator, conventionally known materials such as cotton, rayon, acetate, nylon, polyester, polyolefins such as PP and PE, polyimide, aramid, etc. are used alone or in combination. The bulk density of the nonwoven fabric is not particularly limited as long as sufficient battery characteristics can be obtained by the impregnated polymer gel electrolyte. The thickness of the nonwoven fabric separator is the same as that of the electrolyte layer, and is preferably 5 to 200 μm, and particularly preferably 10 to 100 μm.
[0066] The separator may also be a separator in which a heat-resistant insulating layer is laminated on a porous substrate (a separator with a heat-resistant insulating layer). The heat-resistant insulating layer is a ceramic layer containing inorganic particles and a binder.
[0067] As described above, the nonaqueous electrolyte secondary battery according to the present embodiment has a maximum depth of discharge (DOD) during discharge. max [%] is 89 or less DOD max ≦99. Here, "Depth of Discharge (DOD)" is a value that indicates the discharge state of a secondary battery, and is expressed as a percentage [%] of the ratio of the discharge amount to the rated capacity. Therefore, when the DOD at a certain point in the discharge process is 90%, it means that 90% of the full charge amount has been discharged. Therefore, "DOD max [%] is 89 or less DOD max "Used so as to satisfy 89% or more and 99% or less" means that the discharge process is carried out so that the maximum value of the depth of discharge (DOD) in the discharge process of the battery is 89% or more and 99% or less. In addition, a battery is usually used by repeating charge and discharge processes, and the maximum value of DOD in one discharge process is within the above range, which is within the scope of the present invention. However, if the same battery is discharged multiple times, the effect of the present invention can be more effectively achieved if the maximum value of DOD is within the above range for preferably 10% or more, more preferably 30% or more, even more preferably 50% or more, still more preferably 70% or more, even more preferably 80% or more, particularly preferably 90% or more, and most preferably 95% or more of the discharge processes. From the viewpoint of further suppressing the decrease in capacity with the progress of charge and discharge cycles, the nonaqueous electrolyte secondary battery according to this embodiment is capable of satisfying 89% or more and 99% or less. max It is more preferable that the above ratio is used so as to satisfy the condition ≦94.
[0068] The nonaqueous electrolyte secondary battery according to the present embodiment is a DOD maxBy setting as above and using the negative electrode, it is possible to further suppress the decrease in capacity after cycle durability. Here, taking the negative electrode as an example, when the depth of discharge (DOD) in the discharge process is 0% (i.e., fully charged state), the negative electrode active material is in a state of maximum expansion by absorbing ions such as lithium ions. Therefore, the negative electrode active material is in a state of plastic deformation and distorted crystal structure. When the discharge process proceeds from that state and the above ions are released, this distortion is eliminated and the crystal structure of the negative electrode active material becomes stable. When the discharge process proceeds further from that state and the above ions are released excessively, the negative electrode active material contracts excessively, and the structure of the electrode is destroyed, such as the negative electrode active material peeling off from the gel-forming polymer and other electrode constituent components. As a result, it is considered that the capacity decreases as the charge-discharge cycle proceeds. On the other hand, in the nonaqueous electrolyte secondary battery according to this embodiment, the DOD max It is believed that by setting as above, the decrease in capacity during the progress of charge-discharge cycles due to the destruction of the electrode structure is suppressed. However, this mechanism does not affect the technical scope of the present invention. In addition, even when the electrode active material layer is a positive electrode active material layer, the effect of the present invention is achieved by a similar mechanism. However, from the viewpoint of the larger expansion and contraction described above, the present invention is particularly effective when the electrode active material layer is a negative electrode active material layer.
[0069] In view of the above, according to another aspect of the present invention, there is provided a method for using a non-aqueous electrolyte secondary battery comprising an electrode in which an electrode active material layer containing an electrode active material and a gel-forming polymer is disposed on the surface of a current collector, and an electrolyte layer in which a separator disposed adjacent to the electrode active material layer is impregnated with an electrolyte solution, the volume percentage y [%] of the gel-forming polymer contained in the electrode active material layer satisfying 6.9≦y≦7.8, max [%] is 89 or less DOD max There is also provided a method of use in which the battery is discharged so as to satisfy the condition of ≦99. By using the nonaqueous electrolyte secondary battery in this manner, it is possible to continuously use the battery for a long period of time while suppressing a decrease in capacity during the progress of charge-discharge cycles.
[0070] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a lithium ion secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The positive electrode current collector plate 25 and the negative electrode current collector plate 27 may be made of the same material or different materials.
[0071] [Positive and negative leads] Although not shown, the current collector 11 and the current collector plate (25, 27) may be electrically connected via a positive electrode lead and a negative electrode lead. As the constituent materials of the positive electrode and the negative electrode lead, materials used in known lithium ion secondary batteries may be similarly adopted. Note that the part removed from the exterior is preferably covered with a heat-resistant insulating heat shrink tube or the like so as not to come into contact with peripheral devices or wiring, causing a current leak and affecting products (e.g., automobile parts, particularly electronic devices, etc.).
[0072] [Battery exterior] As the battery exterior body, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum, which can cover the power generating element as shown in FIG. 1, can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, an aluminate laminate is more preferable as the exterior body because the collective pressure applied to the power generating element from the outside can be easily adjusted and the thickness of the electrolyte layer can be easily adjusted to the desired thickness.
[0073] The nonaqueous electrolyte secondary battery according to the present embodiment can exhibit excellent cycle durability and output characteristics (rate characteristics), and therefore the lithium ion secondary battery according to the present embodiment can be suitably used as a driving power source for EVs and HEVs.
[0074] Although one embodiment of the positive electrode material for lithium ion secondary batteries has been described above, the present invention is not limited to the configuration described in the above embodiment, and can be appropriately modified based on the description of the claims.
[0075] For example, the type of battery to which the positive electrode material for lithium ion secondary batteries according to the present embodiment is applied includes a bipolar battery including a bipolar electrode having a positive electrode active material layer electrically bonded to one surface of a current collector and a negative electrode active material layer electrically bonded to the opposite surface of the current collector.
[0076] The following embodiments are also included within the scope of the present invention: the nonaqueous electrolyte secondary battery according to claim 1 having the characteristics of claim 2; the nonaqueous electrolyte secondary battery according to claim 1 or 2 having the characteristics of claim 3; the nonaqueous electrolyte secondary battery according to any one of claims 1 to 3 having the characteristics of claim 4; the nonaqueous electrolyte secondary battery according to any one of claims 1 to 4 having the characteristics of claim 5; the nonaqueous electrolyte secondary battery according to any one of claims 1 to 5 having the characteristics of claim 6; the nonaqueous electrolyte secondary battery according to any one of claims 1 to 6 having the characteristics of claim 7; and the nonaqueous electrolyte secondary battery according to any one of claims 1 to 7 having the characteristics of claim 8. EXAMPLES
[0077] The present invention will be explained in more detail below using examples and comparative examples, but it is not limited to the following examples in any way.
[0078] [Example 1] <Preparation of negative electrode> A powder composition consisting of 87 parts by mass of graphite (average particle size (D50) = 19 μm) and 4.5 parts by mass of SiO (average particle size (D50) = 6.5 μm) as a negative electrode active material, and 0.5 parts by mass of acetylene black (manufactured by Denka Co., Ltd., Denka Black (registered trademark); average particle size (primary particle size): 0.023 μm) as a conductive assistant was mixed at 2000 rpm for 1 minute using a planetary stirring type mixing and kneading device "Awatori Rentaro" (ARE-310, manufactured by Thinky Corporation). Next, an appropriate amount of N-methyl-2-pyrrolidone (NMP), a slurry viscosity adjusting solvent, was added to the powder composition, and the mixture was mixed at 2000 rpm for 2 minutes using the same device. Thereafter, 8 parts by mass of a gel-forming polymer polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP) (Kyner Flex 2851, manufactured by Arkema, proportion of the number of constituent units derived from hexafluoropropylene: 2.4 mol%) dissolved in NMP was further added, and the mixture was mixed in several batches at 2000 rpm for 4 minutes using the same device to prepare a negative electrode slurry. The negative electrode slurry was applied to a Cu foil (thickness 10 μm) placed on a smooth plate so that the negative electrode active material mass (area weight of the negative electrode active material) was 10 mg / cm. 2 The mixture was uniformly applied using a doctor blade and dried on a hot plate at 80° C. for 1 hour. The resulting laminate was then pressed using a roll press. It was then placed in a vacuum dryer and dried at 130° C. for 8 hours under vacuum conditions to produce the negative electrode of this example.
[0079] The thickness of the negative electrode active material layer in the obtained negative electrode was 67 μm. The percentage of the pore volume (x [%]) in the negative electrode active material layer was calculated by the following method, and was found to be 27 [%]. The percentage of the volume of the gel-forming polymer contained in the negative electrode active material layer (y [%]) was calculated by the following method, and was found to be 7.4 [%]. The liquid absorption rate of the gel-forming polymer contained in the negative electrode active material layer was calculated by the following method, and was found to be 45 [%].
[0080] [Calculation of the percentage (x[%]) of pore volume in the negative electrode active material layer] (1) The weight per unit area of the negative electrode active material layer was measured. The weight of each material per unit area of the negative electrode active material layer was calculated from the compounding ratio of the materials. (2) The thickness [A] of the negative electrode active material layer was measured using a micrometer. (3) The thickness [B] of the negative electrode active material layer when the porosity was 0% was calculated using the weight of each material obtained in (1) and the density of each material. (4) The pore volume of the negative electrode active material layer was calculated from the difference (AB) between the measured thickness of the negative electrode active material layer and the calculated thickness of the negative electrode active material layer, and the percentage (x [%]) of the pore volume in the negative electrode active material layer was determined.
[0081] [Calculation of the volume percentage (y[%]) of the gel-forming polymer contained in the negative electrode active material layer] The volume of the gel-forming polymer contained in the negative electrode active material layer was calculated using the weight of the gel-forming polymer obtained in (1) above and the density of the gel-forming polymer, and the percentage (y [%]) of the volume of the gel-forming polymer contained in the negative electrode active material layer was calculated.
[0082] [Measurement of the absorption rate (z) of the gel-forming polymer for the electrolyte] The absorption rate (z) of the gel-forming polymer with respect to the electrolyte was calculated by measuring the weight of the gel-forming polymer before and after immersion in the electrolyte, and using the following formula: Absorption rate (%) = [(weight of gel-forming polymer after immersion in electrolyte solution - weight of gel-forming polymer before immersion in electrolyte solution) / weight of gel-forming polymer before immersion in electrolyte solution] x 100 As a sample, the gel-forming polymer used in each experimental example was dissolved in N-methyl-2-pyrrolidone to prepare a cast film. The cast film was immersed in the electrolyte at 25°C to 50°C for 24 hours. The electrolyte used to determine the liquid absorption rate was obtained by dissolving LiPF61 mol / L in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 3:7).
[0083] <Production of lithium-ion secondary battery (coin cell)> The negative electrode prepared above was punched out to φ15 mm, and was placed opposite a counter electrode Li (φ16 mm), with two separators (polyolefin, thickness: 20 μm) placed between them. Next, a laminate of the negative electrode, separator, and counter electrode (Li metal) was placed on the bottom side of a coin cell (CR2032, material: stainless steel (SUS316)). Furthermore, a gasket was attached to maintain insulation between the electrodes, an electrolyte was injected with a syringe, a spring and a spacer were laminated, and the upper side of the coin cell was overlapped and sealed by crimping to prepare a lithium ion secondary battery (coin cell) of this example. As the electrolyte, an electrolyte obtained by dissolving LiPF61 mol / L in a mixed solvent (volume ratio 3:7) of ethylene carbonate (EC) and diethyl carbonate (DEC) was used.
[0084] [Examples 2 to 23 and Comparative Examples 1 to 11] Lithium ion secondary batteries (coin cells) of Examples 2 to 23 and Comparative Examples 1 to 11 were produced in the same manner as in Example 1 described above, except that the blending amount of the gel-forming polymer (PVdF-HFP) and the pressing conditions during negative electrode production were adjusted so that the volume percentage (y [%]) of the gel-forming polymer contained in the negative electrode active material layer of the negative electrode and the pore volume percentage (x [%]) in the negative electrode active material layer were the values shown in Table 1 below. The values of x, y, and x+y of the negative electrode active material layer in each of the above-mentioned experimental examples are shown in Table 1 below.
[0085] [Cycle durability evaluation] The cycle durability evaluation was performed by placing the lithium ion secondary battery (coin cell) prepared above in a thermostatic chamber set at 25°C. Specifically, as the initial charge / discharge treatment, a constant current discharge was performed at a discharge rate of 0.05C in CCCV mode (cutoff voltage 0.01V), and then a constant voltage discharge (cutoff current 0.01C) was performed after the cutoff voltage was reached. Next, a constant current charge was performed at a charge rate of 0.05C in CC mode until the cell voltage reached 2V.
[0086] Thereafter, as a cycle charge / discharge treatment, constant current discharge was performed at a discharge rate of 0.33C in CC mode. Next, constant current charging was performed at a charge rate of 0.33C in CC mode until the cell voltage reached 2V. This discharge-charge treatment was counted as one cycle, and 100 cycles of cycle charge / discharge treatment were performed. At this time, the depth of discharge (DOD) in the constant current discharge of each cycle was set to the value shown in Table 1 below. The difference between the discharge capacity at the first cycle and the discharge capacity at the 100th cycle was calculated as the discharge capacity decrease [mAh / g]. The measurement results of this discharge capacity decrease are shown in Table 1 below.
[0087] [Table 1]
[0088] From the results shown in Table 1, it can be seen that in the nonaqueous electrolyte secondary batteries of the examples of the present invention, the value of y is within a predetermined range, and the DOD is also set to a value within a predetermined range, and therefore the decrease in capacity after cycle endurance can be suppressed compared to the batteries of the comparative examples. [Explanation of symbols]
[0089] 10a laminated secondary battery, 11' Positive electrode current collector 12 Negative electrode current collector 13 positive electrode active material layer, 15 negative electrode active material layer, 17 electrolyte layer, 19 cell layer, 21 Power generation elements, 25 Positive current collector (positive tab), 27 negative electrode current collector (negative electrode tab), 29 Laminating film.
Claims
1. an electrode having an electrode active material layer disposed on a surface of a current collector, the electrode active material layer including an electrode active material and a gel-forming polymer; an electrolyte layer formed by impregnating a separator disposed adjacent to the electrode active material layer with an electrolytic solution; having A volume percentage y [%] of the gel-forming polymer contained in the electrode active material layer satisfies 6.9≦y≦7.8, and The maximum depth of discharge (DOD) during discharge max [%] is 89≦DOD max ≦99.
2. 2. The nonaqueous electrolyte secondary battery in accordance with claim 1, wherein x and y satisfy 30.8≦x+y≦38.9, where x [%] is a percentage of the pore volume in the electrode active material layer.
3. 3. The nonaqueous electrolyte secondary battery in accordance with claim 1, wherein a volume percentage y [%] of the gel-forming polymer satisfies 7.2≦y≦7.
8.
4. 3. The nonaqueous electrolyte secondary battery in accordance with claim 1, wherein a volume percentage y [%] of the gel-forming polymer satisfies 7.2≦y≦7.
4.
5. The maximum depth of discharge (DOD) during discharge max [%] is 89≦DOD max 3. The nonaqueous electrolyte secondary battery according to claim 1, wherein the nonaqueous electrolyte secondary battery is used so as to satisfy a moisture content of ≦94.
6. 3. The nonaqueous electrolyte secondary battery in accordance with claim 1, wherein the electrode active material layer is a negative electrode active material layer containing a silicon-based negative electrode active material as the electrode active material.
7. 7. The nonaqueous electrolyte secondary battery in accordance with claim 6, wherein the silicon-based negative electrode active material comprises a silicon oxide.
8. 7. The nonaqueous electrolyte secondary battery in accordance with claim 6, wherein the content of said silicon-based negative electrode active material in said negative electrode active material layer is more than 0 mass % and not more than 5 mass %.
9. an electrode having an electrode active material layer disposed on a surface of a current collector, the electrode active material layer including an electrode active material and a gel-forming polymer; an electrolyte layer formed by impregnating a separator disposed adjacent to the electrode active material layer with an electrolytic solution; having A method for using a nonaqueous electrolyte secondary battery, wherein the volume percentage y [%] of the gel-forming polymer contained in the electrode active material layer satisfies 6.9≦y≦7.8, max [%] is 89 or less DOD max A method of use in which discharge is performed so that the discharge rate satisfies ≦99.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2014063671A
